From Bank Preparation to Clinical Use of Homologous Skin Allografts in Wound Healing: A Sustainable Approach - Amoroso, Laura; Agueci, Serena; Pianigiani, Elisa; Ierardi, Francesca; Calabrese, Laura; Rubegni, Pietro; Tognetti, Linda (Life (Basel, Switzerland), 2024)
Given progressive population ageing and the increase in the number of patients with comorbidities, the management of chronic and/or hard-to-heal wounds (HHWs) nowadays represents a common problem in many clinical settings. In these cases, standard strategies may not be sufficient. Autologous grafting represent the gold standard for permanent wound closure, but is almost never realized when the skin loss is extensive/the patient is young. The grafting of homologous skin/dermal tissue procured from cadaver donors (i.e., allografting) represents the best alternative, especially when the dermal component is lost. This request supports the activities of skin bank establishments (including donor screening, skin procurement, processing, storage, and distribution) that are regulated by specific guidelines and need to continuously meet quality standard requirements. The aim of this work is to both give specific insights of all the procedures implied in allograft preparation as well as an overview of their practical application in the treatment of different HHWs. The particular characteristics of each skin/dermal allograft released by Siena Skin Bank (cryopreserved/glycerol-preserved skin/de-epidermized dermis, acellular lyophilized de-epidermized dermis/reticular dermis) are also discussed. The exemplificative series of HHWs managed in the Dermatology Department of Siena were classified according their etiology into post-traumatic, vascular (arterial/venous/mixed/lymphatic), inflammatory, surgical, and heat/chemical burns. Globally, the clinical advantages obtained include: acceleration of healing process, pain sparing, resistance to bacterial contamination, dermal regeneration (instead of scarring), and better aesthetic–functional outcome.